Analisis Sistem Informasi Eksekutif menggunakan User Experience Questionnaire (UEQ) - Putra, I Nyoman Tri Anindia; Kartini, Ketut Sepdyana; Aditama, Putu Wirayudi; Tahalea, Sylvert Prian (International Journal of Natural Science and Engineering, 2021)
To increase user satisfaction with information systems requires analysis and testing of the system. The User Experience Questionaire (UEQ) is a tool used to measure the level of user satisfaction with a system through a questionnaire. This study focuses on the analysis of executive information systems at STMIK STIKOM Indonesia in order to improve information systems, especially in system design. The six rating scales that will be sought in this study include attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Based on the test results using the UEQ method, the executive information system STMIK STIKOM Indonesia obtained Good results.